The Criticism of Monarchy in Isocrates’ Cyprian Orations - Kossarev, Danil (Hyperboreus, 2024)
The Cyprian Orations, addressed by Isocrates to his former student Nicocles on the occasion of the latter’s ascension to the throne of Salamis, have caused discussions among scholars about the orator’s political thought for a long time. Do these works clearly outline Isocrates’ monarchical preferences, or are they nothing but a set of advice to a young king on how, according to Isocrates, he should behave as a king? The aim of this article is to highlight some passages in which Isocrates covertly or openly criticizes monarchical power.